TERMINATION OF EMPLOYMENT CONTRACT DUE TO CIRCUMSTANCES BEYOND THE CONTROL OF THE PARTIES (THEORETICAL AND LEGAL ANALYSIS) - Murodullayev Dostonjon Nigmatullo o‘g‘li (Scholar Express Journals, 2022)
The research focuses on the application of the concepts of "the employment contract", "termination of the employment contract" and "dismissal" and cases when the employment contract was terminated due to circumstances beyond the control of the parties. Though the Labor Code of the Republic of Uzbekistan clearly defines the grounds for termination of an employment contract in cases beyond the control of the parties, there is no mechanism for applying these grounds in practice. In other words, there are no rules for terminating an employment contract, on what basis, in what order and for how long
Keywords: employment; employee; termination of the employment contract; dismissal